Evaluation of the aquifer system and groundwater quality of the north-western districts of Bangladesh for development potential - Islam, Kamrul; Rahman, M. Saidur; Ali, M. Hazrat; Hossain, A.F.M. Afzal; Alam, M. Jahangir; Zahid, Anwar (© 2016 Published by BRAC University, 2017)
This article was published in the BRAC University Journal [© 2016 Published by BRAC University].